All‐Solid‐State Batteries with Anodeless Electrodes: Research Trend and Future Perspective - Sang‐Jin Jeon; Un‐Hyuk Kim; Sang Hoon Kwag; Jin‐Wook Min; Dong‐Won Kim; Hansu Kim; Yun‐Jung Lee; Yun‐Chae Jung (Advanced Materials Interfaces)
Abstract All‐solid‐state batteries (ASSBs) are promising “beyond lithium‐ion batteries” candidates owing to their high energy density and safety. Anodeless electrodes are critical components for enabling these attributes, offering a fundamentally distinct mechanism compared to conventional anode systems. This unique mechanism of anodeless electrodes has garnered significant scientific interest and has prompted extensive research. Based on recent advancements, this perspective provides comprehensive insights into anodeless electrode materials in ASSBs and outlines prospective research directions to address the remaining challenges and further ASSB performance optimization.